Development of Socio-Scientific Issues-Based Learning Modules to Train Students' Critical Thinking Skills in Global Warming for 10 th Grade Senior High School/MA - Indriani Savitri; Mimi Herman (Universitas Lampung, 2026)
This study aims to test the validity and practicality of socio-scientific issues-basedlearning modules to train students' critical thinking skills in global warming. The method used in this study was Research and Development (R&D) using the 4-D development model. The testsubjects were 35 students in class X.E1 at SMA Negeri 2 Batusangkar. The data analysistechnique was a validity and practicality test of expert validation sheets and respondentquestionnaires, as well as a three-tier critical thinking test. The results showed that the validityof the material in the learning module based on socio-scientific issues was 88%, constructvalidation was 100%, and language validation was 95%. The results of the practicality test fromteacher and student questionnaires were 86% and 93%, respectively. The level of students'critical thinking improved from 55% (fair) to 86% (very good). Based on the results of thestudy, it can be concluded that the socio-scientific issues-based learning module to trainstudents' critical thinking skills in global warming is very valid and very practical to use.